Chronic obstructive pulmonary disease and heart failure: research and clinical practice in primary care - Francesco Chiumeo; Stefania Folloni (Italian Journal of Medicine, 2015)
The treatment of chronic obstructive pulmonary disease (COPD) and comorbidities, increasing with age, is the challenge that nowadays health care systems are facing to better care treat these patients. For this reason a clinical trial was conducted in the province of Trento by a group of 30 volunteer general practitioners members of SNAMID (Scientific Society for Continuing Medical Education of General Practitioners). The objectives were to identify: i) prevalence of COPD in patients (65-98 years) in the province of Trento; ii) presence and incidence of heart failure (HF) in COPD patients; iii) early detection of other chronic diseases; and iv) improving electronic medical records (EMR) as an innovation way of professional care management. From May 2011 to October 2013, 17 doctors completed the two-year work using the EMR. The studied patients were men and women (65-98 years), suffering from COPD; the considered data included: anthropometric information, smoking status, International Classification of Diseases (ICD)-9 diagnosis of COPD, HF and chronic diseases, specific blood and instrumental tests. The extracted results were then linked with data of sentinel therapies, collected by the EMR. The database obtained identified patients with COPD or HF not previously recognized with ICD-9 diagnosis. The study identified the sentinel drugs chosen for COPD and HF, excluding other drugs not selective for the study or confusing for a proper statistical evaluation.